2024
DOI: 10.1021/acsomega.3c10192
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Stable Low-Energy Gallium Oxide (Ga2O3) Polytypes: Insights into Electronic and Optical Properties from First Principles

Arthi Devamanoharan,
Vishnukanthan Venkatachalapathy,
Vasu Veerapandy
et al.

Abstract: This study provides a comprehensive analysis of the electronic and optical properties of low-energy gallium oxide (Ga 2 O 3 ) polytypes not considered earlier. Among these polytypes, the monoclinic structure (β-Ga 2 O 3 ) holds significant relevance for both research and practical applications due to its superior stability under typical conditions. The primary aim of this research is to identify new and stable Ga 2 O 3 polytypes that may exist under zerotemperature and zero-pressure conditions. To achieve this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 63 publications
0
0
0
Order By: Relevance
“…The volume data was fitted with a third-order Birch–Murnaghan equation of state: 31–33 where V 0 is the volume at zero pressure, B 0 is the bulk modulus at ambient pressure, and is a parameter for the pressure derivative. The fitting of the Birch–Murnaghan equation indicated that the isothermal bulk modulus B 0 for the Ga 2 O 3 NCs was estimated as 137.34 GPa, much higher than that (85.9 GPa) of the bulk counterpart 34 (Fig. S9†).…”
Section: Resultsmentioning
confidence: 96%
“…The volume data was fitted with a third-order Birch–Murnaghan equation of state: 31–33 where V 0 is the volume at zero pressure, B 0 is the bulk modulus at ambient pressure, and is a parameter for the pressure derivative. The fitting of the Birch–Murnaghan equation indicated that the isothermal bulk modulus B 0 for the Ga 2 O 3 NCs was estimated as 137.34 GPa, much higher than that (85.9 GPa) of the bulk counterpart 34 (Fig. S9†).…”
Section: Resultsmentioning
confidence: 96%